Optimum Availability of Standalone Photovoltaic Power Systems for Remote Housing Electrification - Tamer Khatib; Wilfried Elmenreich (International Journal of Photoenergy)
The availability of PV systems is discussed to determine the optimum availability at which standalone PV systems must be designed. Optimization methods and PV systems software, such as HOMER and PV.MY, were used for this purpose. Six PV systems with six availability levels were analyzed, in terms of wasted energy, cost of energy, battery usage, and power shortages, using real meteorological data. Results show that PV systems with 99% availability are recommended, because of their high reliability and favorably wasted energy.